2012
DOI: 10.1021/jf301944e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mannanase from a Novel Mannanase-Producing Bacterium

Abstract: Locust bean gum (LBG) was employed to screen mannanase-producing bacteria. The bacterium with highest mannanase ability was identified as Paenibacillus cookii. It revealed highest activity (6.67 U/mL) when cultivated in 0.1% LBG with 1.5% soytone and 0.5% tryptone after 4 days incubation at 27 °C. Its mannanase was purified to electrophoretical homogeneity after DEAE-Sepharose and Sephacryl S-100 separation. The purified mannanase, with an N-terminus of GLFGINAY, had pH and temperature optimum at 5.0 and 50 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…The utilization of mannanases along with other xylanases can equally facilitate lignin removal in pulp bleaching. On the other hand, it showed relatively high activity on guar, xanthan, and fenugreek gums, which was significantly different from the report by Yin et al [33]. The mannanase can degrade the polysaccharides including mannan, glucomannan, and galactomannan.…”
Section: Hydrolytic Propertiescontrasting
confidence: 79%
“…The utilization of mannanases along with other xylanases can equally facilitate lignin removal in pulp bleaching. On the other hand, it showed relatively high activity on guar, xanthan, and fenugreek gums, which was significantly different from the report by Yin et al [33]. The mannanase can degrade the polysaccharides including mannan, glucomannan, and galactomannan.…”
Section: Hydrolytic Propertiescontrasting
confidence: 79%
“…1B). The same pH of optimal Bacillus β-mannanase activity has been reported by Yin et al [30] and Bo et al [35]. However, Pangsri et al [36] and Zhou et al [37] have characterized Bacillus-derived β-mannanases with optimal activity at pH 6 and 9.5, respectively.…”
Section: Enzyme Characterizationsupporting
confidence: 62%
“…The β-mannanase activities obtained using LBG as mannan source were higher than the values corresponding to mannanase production by many Bacillus strains (activities ranging from 0.001 to 0.8 U mL −1 ) as described by Adebayo-Tayo et al [18] and Abe et al [28]. However, higher enzyme titers were reported by Srivastava et al [29] and Yin et al [30] who showed that the extracellular β-mannanase activity produced by Bacillus sp. CFR1601 and Paenibacillus cooki, was of 12.62 and 6.67 U mL −1 , respectively.…”
Section: Screening and Identification Of Extracellular Mannanase Prodmentioning
confidence: 67%
See 1 more Smart Citation
“…β ‐mannanase has been identified and produced in many organisms, including bacteria, fungi, actinomycetes, plants and mollusks , . At present, research on β ‐mannanase has mainly focused on gene cloning, expression, characterization, production and structural analysis , .…”
Section: Introductionmentioning
confidence: 99%